Aspergillus-fermented Jatropha curcas seed cake: proximate composition and effects on biochemical indices in Wistar rats - FAOZIYAT, SULAIMAN ADENIKE; AMINA, AHMED EL-IMAM MUSTAPHA; ADEYEMO, AFEEZ ADEYEMI; MUHAMMED, RIHANAT BUKOLA; SULAIMAN, ABIODUN MUINAT; ALIYU, ABDULFATTAH ORELOPE; ADEYEMI, OLUYOMI STEPHEN (Biological Letters, 2015)
This study evaluated Jatropha curcas seed cake fermented by Aspergillus niger for use as a potential source of protein in animal feed production. Wistar rats were randomly assigned to 4 groups (A–D, of 3 rats each) and fed different protein-rich diets for 4 weeks. Group 1 (control) was fed with soybean as a protein source, while Groups 2, 3, and 4 were given feeds supplemented instead with Aspergillus-fermented J. curcas, unfermented J. curcas, and a mix of Aspergillus-fermented J. curcas and soybean (1:1), respectively. At the end of the experiment, rats were sacrificed, and their serum and vital organs were harvested for further analyses. Proximate analyses of the various diet combinations showed significant (P < 0.05) variations in crude protein, crude fibre, ether extract, and ash content. Enzyme assays (alanine transaminase, aspartate transaminase, and alkaline phosphatase) in rat serum and tissue homogenates indicate that the detoxification of J. curcas kernel cake by A. niger fermentation is viable and promising. Body weight generally did not differ significantly between the groups, but all rats put on weight in week 1 (Group 2 most strongly). The initial weight gain was followed by a slight decreasing trend in all groups in weeks 2–4, probably due to an adaptation mechanism. One rat fed with the unfermented cake (Group 3) died in week 2, confirming that the cake is not safe for direct consumption until it is processed. Our data support further use of Aspergillus-fermented J. curcas as an alternative protein source in animal feed preparation.